Kubernetes best practices blueprints for building successful applications on Kubernetes - Burns, Brendan 1976-; Villalba, Eddie; Strebel, Dave; Evenson, Lachlan (O'Reilly, 2019)
You've learned everything there is to know about Kubernetes. Now it's time to put that knowledge into practice. With this practical book, tech leads, DevOps engineers, developers, and architects will learn real-world best practices for putting Kubernetes into action with actual applications. You'll understand how to build and deploy complete solutions in Kubernetes-everything from CI/CD to application design, deployments, and experiments. You'll also learn how other companies have delivered solutions in Kubernetes
Keywords: Kubernetes